An experimental and numerical investigation of core damage size in honeycomb sandwich panels subject to low-velocity impact. (15th December 2020) - Wowk, D.; Reyno, T.; Yeung, R.; Marsden, C.
Highlights: Core damage depth is dependent on the height of the adhesive fillet. Core damage depth is independent of the dent depth, impact velocity, impactor size and mass. Core damage depth is independent of the density and configuration of the honeycomb core. The width of the core damage is the same as the width of the facesheet dent. Abstract: The load carrying capability of honeycomb sandwich panels has been shown to be reduced due to core damage resulting from low-velocity impacts. Knowing the size of the core damage region would aid in predicting the reduction in residual strength of such panels. The current study determines the width and depth of the core damage region in four aluminum panels containing barely visible impact damage. Different honeycomb core configurations and impact parameters were considered experimentally using a pendulum apparatus and numerically using dynamic finite element simulations. One retired aircraft panel that contained damage from in-service impacts was also considered. Destructive sectioning showed that the core damage depth was constant within each panel for different depths of surface dents, impact velocity, impactor radius and mass. The depth of the core damage was proven to be dependent only on the height of the adhesive fillet that joins the facesheet to the core. The width of the core damage was contained to a region directly below the surface dent in the facesheet. The experimental and numerical results also showed that the configuration of the cellular core did not have a significant influence on the core damage depth.